In defense of self - Clark, William R. (Oxford University Press, 2008)
William Clark's In Defense of Self offers a refreshingly accessible tour of the immune system, putting in layman's terms essential information that has been for too long the exclusive province of trained specialists. Clark explains how the immune system works by using powerful genetic, chemical, and cellular weapons to protect us from the vast majority of disease-causing microbes-bacteria, viruses, molds, and parasites. Only those microbes our bodies need to help us digest food and process vitamins are admitted